Resistome in the indoor dust samples from workplaces and households: a pilot study - Klvanova, Eva; Videnska, Petra; Barton, Vojtech; Bohm, Jan; Splichalova, Petra; Koksova, Viktorie; Urik, Milan; Lanickova, Barbara; Prokes, Roman; Budinska, Eva; Klanova, Jana; Borilova Linhartova, Petra (Frontiers in Cellular and Infection Microbiology, 2024)
The antibiotic resistance genes (ARGs) limit the susceptibility of bacteria to antimicrobials, representing a problem of high importance. Current research on the presence of ARGs in microorganisms focuses mainly on humans, livestock, hospitals, or wastewater. However, the spectrum of ARGs in the dust resistome in workplaces and households has gone relatively unexplored. This pilot study aimed to analyze resistome in indoor dust samples from participants’ workplaces (a pediatric hospital, a maternity hospital, and a research center) and households and compare two different approaches to the ARGs analysis; high-throughput quantitative PCR (HT-qPCR) and whole metagenome shotgun sequencing (WMGS). In total, 143 ARGs were detected using HT-qPCR, with ARGs associated with the macrolides, lincosamides, and streptogramin B (MLSB) phenotype being the most abundant, followed by MDR (multi-drug resistance) genes, and genes conferring resistance to aminoglycosides. A higher overall relative quantity of ARGs was observed in indoor dust samples from workplaces than from households, with the pediatric hospital being associated with the highest relative quantity of ARGs. WMGS analysis revealed 36 ARGs, of which five were detected by both HT-qPCR and WMGS techniques. Accordingly, the efficacy of the WMGS approach to detect ARGs was lower than that of HT-qPCR. In summary, our pilot data revealed that indoor dust in buildings where people spend most of their time (workplaces, households) can be a significant source of antimicrobial-resistant microorganisms, which may potentially pose a health risk to both humans and animals.